The Adoption of Innovative Proposals as Risky Choice: A Model and Some Results - Dickson, John W. (Academy of Management Journal, 1976)
Adoption of an innovative proposal was postulated to be a function of (1) the expected value of the possible outcomes, (2) their range or variance, and (3) the expectancy of achieving a target outc...